Demokratisasi di Perdesaan Melalui Badan Perwakilan Desa - Hubertus Hasan Ismail (Centre for Public Policy and Management Studies, 2004)
The founding of BPD as an active institution in accommodating and articulating the interest of village community in village government practice is become the basic spirit of Law of Republic Indonesia Number 22/1999 on Local Government. This Law has the goal abolishing destruction practices toward potential economics and the ongoing practice of democratization in village community. Nevertheless, the institutionalization of BPD apparently has not yet strengthened the democratization process in this level. This indication emerges in the membership practices of BPD, the function realization and the decision making process which happened in this institution. Interpretation bias, mismatch between the membership requirement and the real condition of village community and unrepresentative value in membership of BPD constitute visualization of undemocratic practices of BPD.Kata kunci: demokratisasi, keanggotaan BPD, tugas dan wewenang BPD, keterwakilan, proses pengambilan keputusan